2013
DOI: 10.1128/jvi.03390-12
|View full text |Cite|
|
Sign up to set email alerts
|

The TobamovirusTurnip Vein Clearing Virus30-Kilodalton Movement Protein Localizes to Novel Nuclear Filaments To Enhance Virus Infection

Abstract: Plant viruses overcome the barrier of the plant cell wall by encoding cell-to-cell movement proteins (MPs), which direct newly replicated viral genomes to, and across, the wall. The paradigm for how a single MP regulates and coordinates these activities is the Tobacco mosaic virus (TMV) 30-kDa protein (MP TMV ). Detailed studies demonstrate that TMV multiplies exclusively in the cytoplasm and have documented associations of MP TMV with endoplasmic reticulum (ER) membrane, microtubules, and plasmodesmata throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 67 publications
5
37
0
Order By: Relevance
“…These proteins contain NLS motifs and protein-protein and proteinnucleic acid (RNA and/or DNA) interaction domains that allow them to bind to host promoters (Lukhovitskaya et al, 2013a) or to recruit the viral RNA, other viral proteins, and/or host factors to facilitate viral cell-tocell and/or systemic movement through the phloem (see references below). Well-characterized plant virus proteins of this category include the ORF3 protein of Groundnut rosette virus (GRV; unassigned family, genus Umbravirus), the CP of Potato leaf roll virus (family Luteoviridae), the genome-linked viral protein of Potato virus A (family Potyviridae), the 2b suppressor of RNA silencing of Cucumber mosaic virus (family Bromoviridae), the P7a movement protein of Beet black scorch virus (family Tombusviridae), the CP of Alfalfa mosaic virus (family Bromoviridae), the P30 movement protein encoded by Turnip vein clearing virus (family Virgaviridae), and the P14 suppressor of RNA silencing and P25 of Beet necrotic yellow vein virus (family Virgaviridae; Haupt et al, 2005b;Kim et al, 2007;Rajamäki and Valkonen, 2009;González et al, 2010;Herranz et al, 2012;Wang et al, 2012;Chiba et al, 2013;Levy et al, 2013). Other viral proteins found in the nucleolus include the P3 protein of Tobacco etch virus (family Potyviridae) and the CP of Ourmia melon virus (unassigned family, genus Ourmiavirus), but the function of these nucleolar localizations is unknown (Taliansky et al, 2010;Crivelli et al, 2011;Rossi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins contain NLS motifs and protein-protein and proteinnucleic acid (RNA and/or DNA) interaction domains that allow them to bind to host promoters (Lukhovitskaya et al, 2013a) or to recruit the viral RNA, other viral proteins, and/or host factors to facilitate viral cell-tocell and/or systemic movement through the phloem (see references below). Well-characterized plant virus proteins of this category include the ORF3 protein of Groundnut rosette virus (GRV; unassigned family, genus Umbravirus), the CP of Potato leaf roll virus (family Luteoviridae), the genome-linked viral protein of Potato virus A (family Potyviridae), the 2b suppressor of RNA silencing of Cucumber mosaic virus (family Bromoviridae), the P7a movement protein of Beet black scorch virus (family Tombusviridae), the CP of Alfalfa mosaic virus (family Bromoviridae), the P30 movement protein encoded by Turnip vein clearing virus (family Virgaviridae), and the P14 suppressor of RNA silencing and P25 of Beet necrotic yellow vein virus (family Virgaviridae; Haupt et al, 2005b;Kim et al, 2007;Rajamäki and Valkonen, 2009;González et al, 2010;Herranz et al, 2012;Wang et al, 2012;Chiba et al, 2013;Levy et al, 2013). Other viral proteins found in the nucleolus include the P3 protein of Tobacco etch virus (family Potyviridae) and the CP of Ourmia melon virus (unassigned family, genus Ourmiavirus), but the function of these nucleolar localizations is unknown (Taliansky et al, 2010;Crivelli et al, 2011;Rossi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the P30 protein from the Tobamovirus turnip vein clearing virus (TVCV) encodes a nuclear localization signal required for both cellto-cell and systemic virus movement (19). Association of the TVCV P30 protein with nuclear F-actin filaments was hypothesized to alter gene expression and promote virus infection (19). These studies provide evidence that virus interactions with host-associated transcriptional regulators can modulate systemic virus movement.…”
Section: Significancementioning
confidence: 96%
“…Similarly, overexpression of KELP resulted in the partial relocation of P30 to the nucleus and prevented ToMV cell-to-cell and systemic movement. Furthermore, the P30 protein from the Tobamovirus turnip vein clearing virus (TVCV) encodes a nuclear localization signal required for both cellto-cell and systemic virus movement (19). Association of the TVCV P30 protein with nuclear F-actin filaments was hypothesized to alter gene expression and promote virus infection (19).…”
Section: Significancementioning
confidence: 99%
“…To answer this question, we engineered a TVCV replicon that express a functional fusion of MP TVCV with GFP or RFP, and used these infectious clones to examine the distribution of MP TVCV during TVCV infection in Arabidopsis Col-0 and N. benthamiana, both susceptible hosts. 5 Surprisingly, we found that TVCV exhibits three distinct differences from TMV: (1) …”
Section: Please Scroll Down For Articlementioning
confidence: 95%